2002
DOI: 10.1051/0004-6361:20020616
|View full text |Cite
|
Sign up to set email alerts
|

A method for the prediction of relative sunspot number for the remainder of a progressing cycle with application to cycle 23

Abstract: Abstract. In this paper, we investigate the prospect of using previously occurring sunspot cycle signatures to determine future behavior in an ongoing cycle, with specific application to cycle 23, the current sunspot cycle. We find that the gross level of solar activity (i.e., the sum of the total number of sunspots over the course of a sunspot cycle) associated with cycle 23, based on a comparison of its first several years of activity against similar periods of preceding cycles, is such that cycle 23 best co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In this work, we predicted the start and peak time of cycle 24 by a proposed method using similar phases for the descending phase of cycle 23, instead of similar cycles (Wang & Han 1997). Li et al (2002Li et al ( , 2005 also studied the similarity of cycle 23 with other cycles and the prediction for cycle 24.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we predicted the start and peak time of cycle 24 by a proposed method using similar phases for the descending phase of cycle 23, instead of similar cycles (Wang & Han 1997). Li et al (2002Li et al ( , 2005 also studied the similarity of cycle 23 with other cycles and the prediction for cycle 24.…”
Section: Discussionmentioning
confidence: 99%
“…3 For longterm ongoing cycle predictions, people usually use the curvefitting function (Waldmeier 1935;Hathaway et al 1994;Li 1999;Du 2011;Li et al 2017) or use the similarity of solar cycles, e.g., Li et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…The application of the method to cycle 23 results in very successful predictions of SMSNs (errors ≤ 30%) for the 96 months from August 1996 to July 2004 [17,18] . Several methods have been used to make this kind of prediction and Li et al [19] proposed a method for the prediction of SMSNs for the remainder of a progressing solar cycle. They found that cycle 2 is the similar cycle of cycle 23.…”
mentioning
confidence: 99%